Forging Futures: The Role of Education in Shaping the Chinese Elite in Surabaya (1880s-1942) - Rahayu, Shinta Devi Ika Santhi; Sulistiyono, Singgih Tri; Pugu, Dhanang Respati; Alamsyah, Alamsyah (MOZAIK HUMANIORA, 2023)
This article delves into the crucial role of education in the formation of the Chinese elite in Surabaya from the 1880s to 1942. Education held immense significance within the Chinese community, serving not only as a vehicle for cultural preservation but also as a means of instilling a spirit of equality, positioning education as an integral component of the emancipation movement. The success of Chinese community education is evidenced by the emergence of a cadre of Chinese elites poised to effect transformative changes within their community. Consequently, this article seeks to explain the role of the elite in steering educational objectives to align with contemporary progress and the evolving needs of the Chinese generation. Employing historical methods, the research highlights that the educational pursuits of the Chinese community bore fruit in the form of diverse elite groups. The varied Chinese elite groups that surfaced from the late 19th century to 1942 significantly contributed to the unique narrative of Surabaya's history. Their contributions include catalyzing the Indonesian national spirit and addressing health and education challenges.